Effects of moderate-to-vigorous physical activity on the associations between an insulin resistance surrogate and incident cardiovascular disease and all-cause mortality: a UK Biobank cohort study - Zhu, Ying; Yao, Tianci; Yan, Hongyu; Ke, Qinmei (Frontiers in Endocrinology, 2025)
BackgroundModerate-to-vigorous physical activity (MVPA) and insulin resistance (IR) are associated with cardiovascular disease (CVD). It remains unclear whether different durations of MVPA can modify the associations of the triglyceride glucose-waist height ratio (TyG-WHtR) index, a surrogate for IR, with incident CVD and all-cause mortality, and whether MVPA levels beyond guideline recommendations provide additional benefit.MethodsThis cohort study included 299,928 adults from the UK Biobank study who were free of prevalent CVD at baseline and had complete data on MVPA, the TyG-WHtR index, and relevant covariates. The Cox proportional hazards model was used to assess the independent and joint associations of MVPA and TyG-WHtR with incident CVD and all-cause mortality. A product term of MVPA (< 150, 150–299, 300–599, and ≥ 600 min/week) and TyG-WHtR (tertiles) was included in the model to assess multiplicative interaction.ResultsDuring a median follow-up of 13.8 and 13.6 years, 27,342 CVD cases and 21,258 deaths were observed. MVPA demonstrated a reverse J-shaped association with incident CVD, with a cutoff point at 261.71 min/week, whereas an L-shaped association was observed for all-cause mortality, with risk reduction plateauing at 217.00 min/week. Elevated TyG-WHtR was positively associated with increased risks of incident CVD and all-cause mortality. No significant interaction was found for incident CVD, whereas an interaction effect was observed between 150–299 min/week MVPA and TyG-WHtR tertile 2 on all-cause mortality (HR for interaction, 0.89; 95% CI, 0.81–0.97; p for interaction = 0.012). Compared with the reference group (< 150 min/week MVPA and TyG-WHtR tertile 3), all other combined groups were associated with lower risks. Among participants with MVPA levels of 150–299, 300–599, and ≥ 600 min/week, the extent of risk reduction for these outcomes was similar.ConclusionsOur findings highlight the importance of engaging in guideline-recommended MVPA (150–299 min/week) to reduce all-cause mortality risk, particularly among individuals with moderate IR (TyG-WHtR, 7.01–8.03), who are more likely to benefit. Furthermore, the protective effects of higher levels of MVPA against IR-related risks were consistent with those of guideline-recommended MVPA.